Field Characterization of Landslide-Induced Surge Waves Based on Computational Fluid Dynamics - Wang, Rubin; Ding, Miangang; Wang, Yunzi; Xu, Weiya; Yan, Long (Frontiers in Physics, 2022)
Numerical simulation analysis of landslide-induced surge wave field characteristics offers great insights for engineering practices and is crucial for studying reservoir landslide disaster warning, prevention, and control. Based on the computational fluid dynamics, a numerical calculation model of typical landslide surge was established, and the surge waves caused by the movement of a rigid landslide body along the slope and its propagation process was to simulated and analyzed. The results were compared with classical physical experiments to validate the applicability of the numerical calculation model. Furthermore, effects of the shape and density of landslide body on the surge wave generation, water entry characteristics of landslide body, propagation pattern of surge waves were also studied. It was showed that the starting position of far-field landslide surge negatively correlated with the landslide body density. The shape of landslide body did not substantially impact the far-field starting position, which was mainly influenced by the area of water surface in contact with the sliding body.